Peranan Pemimpin Transformasional dan Transaksional dalam Implementasi Supply Chain terhadap Komitmen dan Kinerja Industri Manufaktur di Malang Raya - Ubud Salim (Jurnal Aplikasi Manajemen, 2010)
The purpose of this research explores the role of transformational and transactional leadership for implementation Supply Chain Management in Indonesia, especially in Malang, East Java. The research variables are transformational and transactional leadership which is connected with commitment and firm performance. The research data is the manufacturing industries (based on BP'S Criteria) in Malang which implement supply chain. The sample for this research based on purposive sampling. The analysis for this research is based on PLS (Partial Least Square). The results for this research show that there is relationship between transactional leadership-and commitment, there is relationship between transformational leadership and commitment to implement supply chain. The other results show that there is negatif significant between transactional leadership and firm performance to implement supply chain. Finally, there is positif relationship between commitmet to implement supply chain with firm performance